4 - Provider expectations and father involvement: learning from experiences of poor “absent fathers” in Gauteng, South Africa - Eddy Mazembo Mavungu (African Sociological Review, 2014)
The phenomenon of absent fathers is prevalent in South Africa and has been singled out as a huge social challenge both in the public and policy debate. However, there has been little scholarly research on how men construct their role as fathers and on factors that constrain paternal involvement. This paper discusses constructions of paternal roles in South Africa, specifically in poor and black communities. The paper also seeks to understand how conceptions of fatherhood shape the type and extent of father involvement. Drawing from focus group discussions held in Gauteng’s poor and black communities with fathers that did not live with their children, this paper argues that fathers are predominantly seen as providers. This prevalent construction of fathers as mainly agents for financial and material support of children and families precludes the emergence of alternative fatherhood roles. Besides, unemployment and poverty affect fathers’ ability to live up to provider expectations. Hence, many fathers retreat or are excluded from playing an active role in their children’s lives. It is essential that social policy and community interventions promote multidimensional fatherhood so as to offer fathers with alternative roles which can be carried out even in situations of unemployment and poverty. Besides, unemployed and poor fathers need social assistance if the society is going to succeed to keep them involved in their children’s lives.